Discursive Boundaries: Code-Switching as Representative of Gibraltarian Identity Construction in M.G. Sanchez’ Rock Black - Gerke, Amanda Ellen (Miscelánea: A Journal of English and American Studies, 2018)
The British overseas territory of Gibraltar situated on the southern tip of the Iberian Peninsula has a population of 30 000 people with a variety of ethnic origins, languages, history, and political affiliations. The recent upsurge in Gibraltarian literature has served not only to draw attention to the dynamic and multifaceted nature of their identity but also to help in the task of identity construction on the part of the Gibraltarians themselves; there is an observable push and pull of affiliation not only in Gibraltar’s cultural artifacts, but also in its language. This article identifies the ways in which code-switching in M.G. Sanchez’ Rock Black represents the Spanish-British conflict, and views language choice as a tool in the construction of group-identity among contemporary Gibraltarians.
Keywords: Gibraltar; M.G. Sanchez; code-switching; Llanito; identity